2021
DOI: 10.3390/ma14123376
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Printing Angle and Load Direction on Flexure Strength in 3D Printed Materials for Provisional Dental Restorations

Abstract: The CAD/CAM techniques, especially additive manufacturing such as 3D printing, constitute an ever-growing part of obtaining different dental appliances and restorations. Of these, provisional restorations are of frequent use in daily dental practice and are the object of this study. Masticatory and parafunctional forces determine flexure on these prostheses. This study investigates the influence of the printing angle and loading direction of the applied force on the flexure strength of two commercially availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 20 publications
1
38
0
3
Order By: Relevance
“…18,20 Previous studies reported the correlation between printing orientation and the strength of 3D-printed resins. 10,23,26 In regard to printing orientation in the present study, the 0degree (horizontal) orientation groups showed the highest flexural strength values in both 3D-printed resins compared to 45-and 90-degree. This could be related to shifting of the layering build of the printing direction from parallel to perpendicular to load direction which can result in strong adhesion within the same layers compared to 45-degree (oblique) and 90-degree (vertical) orientation (Fig 1).…”
Section: Discussionmentioning
confidence: 48%
“…18,20 Previous studies reported the correlation between printing orientation and the strength of 3D-printed resins. 10,23,26 In regard to printing orientation in the present study, the 0degree (horizontal) orientation groups showed the highest flexural strength values in both 3D-printed resins compared to 45-and 90-degree. This could be related to shifting of the layering build of the printing direction from parallel to perpendicular to load direction which can result in strong adhesion within the same layers compared to 45-degree (oblique) and 90-degree (vertical) orientation (Fig 1).…”
Section: Discussionmentioning
confidence: 48%
“…The 19 studies included in this review [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] investigated different types of 3D-printing resins. Five tested the 3Dprinting resin used for the fabrication of interim fixed prostheses, 15,16,19,20,22 seven for denture bases, 12,14,23,25,[27][28][29] one for denture teeth, 26 two for occlusal devices, 11,18 three for orthodontic appliances, 17,21,24 and one for surgical guides 13 (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…None of the included studies described the methods of randomization, allocation, implementation, or access to full trial protocols. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Only one study 28 reported how the sample size was determined.…”
Section: Includedmentioning
confidence: 99%
“…The simulated and experimental size distributions are compared by adopting the analysis of variance (ANOVA) method. 35 Figure 5c shows the simulated internal nanoparticle size distribution after sintering, which can be well fitted by a Gaussian distribution function with a mean diameter of 3.51 nm. As displayed in Supplementary Table 1, the test statistics F is less than the critical values (F-crit) at the 0.05 confidence level, and the P value is larger than 0.05, meaning that the hypothesis on the identity of the two size distributions cannot be rejected.…”
Section: T H Imentioning
confidence: 90%
“…Here, the internal and external nanoparticles’ sintering are both simulated by the Ostwald ripening kinetic model following the procedure of De Smet et al , This simulation begins with the size distribution of the nanoparticles before sintering and ends when the number of nanoparticles in the model evolves to equal the number of nanoparticles after sintering observed in the experiment. The simulated and experimental size distributions are compared by adopting the analysis of variance (ANOVA) method Figure c shows the simulated internal nanoparticle size distribution after sintering, which can be well fitted by a Gaussian distribution function with a mean diameter of 3.51 nm.…”
mentioning
confidence: 99%